Outside material the cover art of Preservation Music - Gowing, Mark (Formist edition, 2017)
"In 2001 friends Andrew Khedoori and Mark Gowing founded an independent record label with a singular aim: to provide like-minded listeners with good music and congruous design. Inevitably, Preservation Music's groundbreaking packaging and cover art became essential to the label's evolution, the course of which you can now trace in Outside Material. As the work of multi-award-winning designer Mark Gowing, the Preservation artwork reflects his commitment to experimentation in typography, photography and graphic abstraction, all with an eye to effective communication. Whatever its printed design, every CD cover employs folded paper as package, offering the listener, or user, an intimate and tactile experience. Consequently, Outside Material's image-drenched pages present music as something more than sound - these creations are material objects to see, hold and cherish. Featuring an illuminating essay by music and arts writer Dan Rule, this lavishly produced volume showcases nine years' worth of thoughtful, music-inspired design. Printed on superior-grade paper, Outside Material presents actual-size reproductions of the label's most distinctive CD covers alongside macro and micro details that further represent the intriguing artwork. An illustrated catalogue of Preservation releases completes the publication." -- Publisher's website